2008
DOI: 10.1159/000112611
|View full text |Cite
|
Sign up to set email alerts
|

Does Sildenafil Affect Uroflowmetry Values in Men with Lower Urinary Tract Symptoms Suggestive of Benign Prostatic Enlargement?

Abstract: Aims: To investigate the effect of sildenafil on uroflowmetry values of patients with lower urinary tract symptoms (LUTS) suggestive of benign prostatic enlargement (BPE). Methods: Thirty-eight consecutive patients and 15 control subjects without voiding symptoms were enrolled in the study. All patients underwent uroflowmetry testing thrice on different occasions. The highest maximum urinary flow rate (Qmax) values with a sufficient voided volume (≧150 ml) were evaluated. The patients and controls w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 33 publications
(25 reference statements)
2
8
1
Order By: Relevance
“…One of the interesting outcomes of our study was that when we combined patients with LUTS and without LUTS in one group, increases in Qmax and Qave values have been defined independently from age and PV. Qmax and Qave increases were not related to micturition and PVR, so that these findings were compliant with the findings from both Guven et al (2009) and Güler et al (2008).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…One of the interesting outcomes of our study was that when we combined patients with LUTS and without LUTS in one group, increases in Qmax and Qave values have been defined independently from age and PV. Qmax and Qave increases were not related to micturition and PVR, so that these findings were compliant with the findings from both Guven et al (2009) and Güler et al (2008).…”
Section: Discussionsupporting
confidence: 91%
“…In our study, significant increase in Qmax and Qave values in LUTS patients have been observed. However, differently from the study of Güler et al (2008), significant increases in Qmax and Qave values were observed in individuals without LUTS who were in age groups similar to those of LUTS patients (Güler et al, 2008).…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…A single dose of the PDE5 inhibitor (50 mg or 100 mg) resulted in an improvement in Q max in the patients. Q ave and the mean voided volumes of the patients also increased while no significant differences were registered in Q max , Q ave and voided volumes of the control group before and after placebo administration [32, 33]. It should be taken into consideration that the study design, and especially the small number of patients, made it rather difficult to draw firm conclusions from these observations.…”
Section: Pde Inhibitors and Lower Urinary Tract Symptoms (Luts) Suggementioning
confidence: 93%
“…Q ave and the mean voided volumes of the patients also increased. In the placebo group, no significant differences in Q max , Q ave and voided volumes were registered [59,60]. It should be taken into consideration that no firm conclusions from these measurements should be drawn because of the study design and the small number of patients.…”
Section: Premature Ejaculationmentioning
confidence: 94%